Requirements fordevelopingheelshoesfor womenwithagestheupper 45years (ModaPalavra e-periódico, 2015)
This paper analyzesmature womenperceptionson theuse of shoes heels as a tool totrace project guidelines. It aims to develop a set ofdesign guidelinesfor better developmentof shoes heelstargeting women with45 years or more. Themethod forbibliographic research wasexploratoryand thedata collection wasdevelopedthrough a quantitativesurveywith dataanalysisperformed usingnon-parametric statisticaltests. The results indicatesthat the use ofshoesis somehowrelatedto the physical characteristics of the consumers, situations of day-to-day appearance,the levelof agreementof the descriptorsassigned towomen's shoesandthe perceptionof comfortinuse.Based on the resultsit was possibleto develop basicdesign guidelinesfor designing shoes heels.
Keywords: design guidelines; female shoes heels; consumers preferences